2011
DOI: 10.1021/jo201172w
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structure, and Properties of Supramolecular Charge-Transfer Complexes between Bis(18-crown-6)stilbene and Ammonioalkyl Derivatives of 4,4′-Bipyridine and 2,7-Diazapyrene

Abstract: 4,4'-Bipyridine and 2,7-diazapyrene derivatives (A) having two ammonioalkyl N-substituents were synthesized. The complex formation of these compounds with bis(18-crown-6)stilbene (D) was studied by spectrophotometry, cyclic voltammetry, (1)H NMR spectroscopy, and X-ray diffraction analysis. In MeCN, π-donor D and π-acceptors A form supramolecular 1:1 (D·A) and 2:1 (D·A·D) charge-transfer complexes. The D·A complexes have a pseudocyclic structure as a result of ditopic binding of the ammonium groups to the crow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 37 publications
0
27
0
2
Order By: Relevance
“…Alkali and alkaline‐earth metal perchlorates can not only react with free macrocyclic moieties of compound 1 but also displace the coordinated ammonium ions from them in complexes of type 1 · 2 . Indeed, upon the addition of Li, Na, K, Mg, Ca, and Ba perchlorates, the absorption spectra of 1 · 2 in acetonitrile show a minor long‐wavelength shift accompanied by intensity increase and appearance of a clear isosbestic point (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alkali and alkaline‐earth metal perchlorates can not only react with free macrocyclic moieties of compound 1 but also displace the coordinated ammonium ions from them in complexes of type 1 · 2 . Indeed, upon the addition of Li, Na, K, Mg, Ca, and Ba perchlorates, the absorption spectra of 1 · 2 in acetonitrile show a minor long‐wavelength shift accompanied by intensity increase and appearance of a clear isosbestic point (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…High thermodynamic stability of these complexes (log K s 1:1 of up to 9.42 in MeCN) is due to the coordination of the ammonioalkyl groups to the crown ether moieties of stilbene 1 (see Chart 1). The “structure‐property” relationship has been studied for related donor‐acceptor complexes, differing in the length of the ammonioalkyl spacers and the type of the central conjugated moiety in the acceptor component . It was shown that these complexes can be regarded as fluorescent molecular sensors for alkaline‐earth metal cations.…”
Section: Introductionmentioning
confidence: 99%
“…Краун-эфиры и их производные широко при-меняются не только в качестве селективных лигандов для катионов металлов, но и как рецепторные модули в дизайне различных супрамолекулярных систем, [1][2][3] например, оптических молекулярных сенсоров (ОМС). [4] Одним из известных свойств краун-эфиров, которое используется в супрамолекулярном дизайне, является способность образовывать сэндвичевые комплексы с от-носительно большими катионами металлов.…”
Section: T P Martyanov Et Alunclassified
“…[29] PCA itself and its stereoselectivity can be controlled by supramolecular preorganization of double bonds, to create the most suitable geometry of the starting dimer. [30][31][32][33][34] We have previously shown that bis-crown stilbenes can form unusual bi-and exotic trimolecular complexes in the reaction with diammonioalkyl derivatives of viologen or cyanine dyes, [35][36] due to the formation of a system of hydrogen bonds. Owing to the spatial preorganization of the donor and acceptor regions of supermolecules, an effective intermolecular charge transfer has been observed in the complexes produced.…”
Section: Introduction Formulation Of the Problem Scope Of Objectivesmentioning
confidence: 99%